(untitled) (Vietnam Journal of Community Medicine, 2023)
Currently, there are many methods for diagnosing and treating TMJ disorders, from conservative treatment to interventional treatment, such as medication, physical therapy, jaw movement exercises, botox injections, surgery, etc. Occlusal splints are a minimally invasive and effective treatment proven in many places. Objectives to evaluate the results of treatment of temporomandibular disorders with occlusal splints at Can Tho the University of Medicine and Pharmacy Hospital in 2021-2022” Research Methods: Sample size 35 patients. A clinical intervention study to evaluate the effect before and after treatment, no control group. Evaluate treatment results after 1 and 6 months: maximal range of jaw movements, pain status, clicking, discomfort when moving jaw.: Take a CBCT film of the TDH joint after 6 months of treatment. Take a film when the patient is not wearing an occlusal splint. The lower jaw is in a physiological resting position to record the position of the mandibular condyle in relation to the temporal bone. Results: VAS joint pain at time T0, T1, T2 decreased by 8.09 ± 1.15, respectively; 3.23 ± 0.97; 0.97 ± 0.80. Rate of patients responding after 6 months of treatment: For pain: 34.3% responded well, 65.7% responded well. For joint sounds: 3.4% respond well, 96.6% respond well. For maximum opening amplitude: 100% good response. Conclusion: Stable occlusal splints help to reduce pain level, reduce clicking level, and increase the maximal opening amplitude and range of motion of the jaw to the side and anterior.